2014
DOI: 10.1128/iai.02098-14
|View full text |Cite
|
Sign up to set email alerts
|

Parasite-Derived Neurotrophic Factor/trans-Sialidase of Trypanosoma cruzi Links Neurotrophic Signaling to Cardiac Innate Immune Response

Abstract: The Chagas' disease parasite Trypanosoma cruzi elicits a potent inflammatory response in acutely infected hearts that keeps parasitism in check and triggers cardiac abnormalities. A most-studied mechanism underlying innate immunity in T. cruzi infection is Toll-like receptor (TLR) activation by lipids and other parasite molecules. However, yet-to-be-identified pathways should exist. Here, we show that T. cruzi strongly upregulates monocyte chemoattractant protein 1 (MCP-1)/CCL2 and fractalkine (FKN)/CX3CL1 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…The concerted action of the interplay of these cytokines will delay the induction of a protective Th1 response and dampen these cells once elicited, thus favoring parasite persistence and host colonization. Notably, it was recently reported that TS upregulates the expression of monocyte chemotactic protein 1 (MCP-1/CCL2) and fractalkine (CX3CL1), which are associated with reduction of inflammation and enhancement of tissue repair (55). Thus, TS seems to be able to manipulate both the innate and adaptive immune responses to control the damage to infected tissue caused by the protective Th1 response.…”
Section: Discussionmentioning
confidence: 99%
“…The concerted action of the interplay of these cytokines will delay the induction of a protective Th1 response and dampen these cells once elicited, thus favoring parasite persistence and host colonization. Notably, it was recently reported that TS upregulates the expression of monocyte chemotactic protein 1 (MCP-1/CCL2) and fractalkine (CX3CL1), which are associated with reduction of inflammation and enhancement of tissue repair (55). Thus, TS seems to be able to manipulate both the innate and adaptive immune responses to control the damage to infected tissue caused by the protective Th1 response.…”
Section: Discussionmentioning
confidence: 99%
“…Tc 13Tul also induced polyclonal non-specific Ig stimulation by in vivo administration. It is worth mentioning that, based on previous studies on Tc TS (Da Silva et al ., 1998; Gao et al ., 2002; Aridgides et al ., 2013; Salvador et al ., 2014), in vivo administration of Tc 13Tul was carried out in the absence of any adjuvant that could mask or potentiate its effect. Tc 13Tul-administered mice showed increased non-specific IgG in sera from day 8 post-inoculation and increased total Ig secretion when their splenocytes were in vitro cultured for 72 h. Neither of these antibodies showed specificity for Tc 13Tul or MBP.…”
Section: Discussionmentioning
confidence: 99%
“…At this respect, it has been shown that purified trans-sialidase of T . cruzi activates newborn cardiomyocytes in vitro through a MyD88-independent pathway, resulting in production of the chemokines MCP-1 and Fractalkine [ 44 ].…”
Section: Discussionmentioning
confidence: 99%